Chinese caregivers’ experiences parenting children with autism spectrum disorder: a descriptive qualitative study - Fan, Xing; Ko, Kyung Soon (Frontiers in Psychiatry, 2025)
BackgroundThis study explored the parenting experiences of caregivers that are raising children with autism spectrum disorder in China by focusing on their emotional experiences as well as perceived roles and responsibilities.ObjectsThe research questions were (1) What are Chinese caregivers’ emotional experiences with their child with autism spectrum disorder? and (2) How do Chinese caregivers perceive their roles and responsibilities related to their children with autism spectrum disorder?MethodQualitative data were gathered through individual interviews with caregivers of children with autism spectrum disorder. The MAXQDA software program was used for data analysis.ResultThe data analysis resulted in four final themes: (a) Unable to abandon the hope that the child will become “ordinary,” (b) The child’s development goes against the expectations of their caregivers, (c) Emotional phases in the caregiver’s responses to diagnosis, and (d) Enduring the life that was given.ConclusionThis study sheds light on the experience of Chinese parents raising children with autism spectrum disorder in a culture that might perceive this disorder differently than the West. This study reflects the authentic parenting dilemmas and intense emotional fluctuations experienced by Chinese caregivers of children with autism spectrum disorder. Understanding these experiences will stimulate the readers’ humanistic thinking, expand their care and compassion toward this group, and benefit society. By exploring the emotional struggles and parenting challenges faced by these parents, the goal is to offer them more tangible understanding and social support.